2018
DOI: 10.1155/2018/3098940
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cell Carcinoma Arises from Interfollicular Layer of Epidermis

Abstract: Background BCC is currently the most common type of skin cancer in humans. Although having a low-grade malignancy and metastatic potential, BCC is locally aggressive and destructive. Despite numerous studies, the origin of BCC, whether arising from the follicular or interfollicular layer, remains controversial. Objectives This study aims to evaluate whether BCC arises from the follicular or interfollicular layer by using immunohistochemical staining. Methods Twenty-three specimens of superficial and nodular BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 25 publications
0
27
1
Order By: Relevance
“…25 The theory that other BCC precursors originate from hair follicles supports the finding because head, face, and neck region contain more hair follicles than any other region of the body. 26,27 However, a discrepancy in the pattern of UV exposure occurred in this study. The proportion of BCC in the trunk as the body's area is typically covered and becomes less exposed has relatively higher tumour density than in the upper and lower extremities.…”
Section: Distribution Of Bcc According To Anatomical Locationcontrasting
confidence: 60%
“…25 The theory that other BCC precursors originate from hair follicles supports the finding because head, face, and neck region contain more hair follicles than any other region of the body. 26,27 However, a discrepancy in the pattern of UV exposure occurred in this study. The proportion of BCC in the trunk as the body's area is typically covered and becomes less exposed has relatively higher tumour density than in the upper and lower extremities.…”
Section: Distribution Of Bcc According To Anatomical Locationcontrasting
confidence: 60%
“…Increasing NMSC incidences demand the development of new therapies and prophylactic measures, as well as the optimization of screenings. NMSC arises from keratinocytes, and can be divided into basal cell carcinoma or cutaneous squamous cell carcinoma (cSCC) depending on the cell type from which tumors develop (Lapouge et al , ; Sanchez‐Danes and Blanpain, ; Tan et al , ). Dysregulated growth factors and their receptors have a deep impact on tumor initiation and progression (Witsch et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…In the year 1903, Krompecher published a book called Der Basalzellenkrebs (The Basal Cell Cancer), which explained that these specific tumors arise from the lowest layer of cells present in the skin [ 6 ]. A recent study performed by Tan et al confirmed that BCC originates within the basal layer of the epidermis and arises from the interfollicular epidermis [ 12 ].…”
Section: The Origin and History Of Keratinocyte Carcinomamentioning
confidence: 99%